Syntaktischer Wandel im Kroatischen am Beispiel der Enklitika - Reinkowski, Ljiljana (Slavistische Beitraege, 2001)
Anyone who deals more thoroughly with the syntax of the Croatian sentence will encounter the problems of enclitics. It will soon be obvious to the Croatian learner, but also to the linguist dealing with the Croatian, that a closer look at the specialist literature reveals that the use of enclitics is not clearly and unequivocally described. Where do the discrepancies in the representations of the enclitics come from? A fundamental assumption of the present study is that the research and discussion of enclitics, based on the construct of a 'Serbo-Croatian' language, did not do justice to the linguistic reality. To correct these omissions and to produce a more accurate and realistic picture of the positioning of enclitics in Croatian and Serbian in the 20th century, the extensive analysis of a text corpus seems sensible and necessary.